Corporate governance and CSR disclosure: International evidence for the period 2006-2016 - Zeynab Miniaoui; Faten Chibani; Khaled Hussainey (Journal of Risk and Financial Management, 2022)
In this paper, the authors examine the impact of corporate governance mechanisms on corporate social responsibility (CSR) disclosure in European and Anglo-Saxon contexts. The study is based on 324 Anglo-Saxon listed corporations and 310 European listed corporations for 11 years from 2006 to 2016 (6813 year-observations). The regression analysis shows that board gender and board age affect CSR disclosure. This study also finds that CEO duality negatively affects CSR disclosure in both contexts. Finally, the study found that the existence of a CSR committee and CSR experts positively affect CSR disclosure in both contexts.
Keywords: 650; corporate governance; Anglo-Saxon context; CSR disclosure; European context